A silent voice [videorecording (DVD)] - Ōima, Yoshitoki (Shout Factory, 2019)
A deaf elementary school girl named Shoko Nishimiya transfers to a new school and meets a boy named Shoya Ishida. Shoya leads the school in bullying Shoko over her disability until she transfers to another school. Immediately, the class bullies Shoya for having bullied Shoko. Shoya loses contact with Shoko, and for years he suffers the consequences of his guilt. Upon entering high school, Shoya finally decides he must find Shoko, determined to make amends for what he did in elementary school.